Implementasi Solar Charging Controller Pada Penggerak Sirkulator Air Kolam Ikan di Kampung Setaman, Kota Depok - Nuralam, Nuralam; Auditia, Ihsan; Purwanti, B. S. R.; Saepudin, Endang; Lestari K., Sri; Adiwinata, Syan Rosyid (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2024)
The community needs-based community service activity of the Industrial Electronics Study Program, Department of Electrical Engineering (JTE) in Kampung Setaman, is an effort to solve the problems of the residents starting from the Covid-19-2020 period, where the residents of Kampung Setaman have around 100 pools, currently the remaining ones have decreased. In the 80s, most homeowners objected to paying for electricity to drive pump motors in fish ponds. As a result, some of the fish ponds died due to inactivity, ironically fish became a source of protein for the residents. Based on this, a solution emerged to create a Solar Power Generation System (PLTS). This is to provide solutions to residents' problems, so that the burden of electricity payments is reduced. Based on the objections to the electricity payment costs that emerged, the design of the PLTS included planning and empowering the pool as a healthy facility and business plan. This PLTS design refers to the concept of electricity distribution from one solar cell house (consisting of 4 cells) to 8 battery units. The aim of this PPIBM is to build a small-scale PLTS of 100 WP (400 WP), with the target of being able to activate 8 units of DC water pump motors for fish pond water circulation. The indicator of PPIBM's success is ensuring the process of storing unused electrical energy from solar cells for each battery. The solar cells are installed on a holo stand at a certain angle according to the direction of the sun, the position can be adjusted. Technical considerations get maximum solar intensity and excess energy can be stored in batteries. PLTS installation refers to the solar cell manual book, the service provider's contribution to the electronic system is so that the electrical energy activates the motor and some of it is stored in the battery (30%). The performance of the PLTS electrical system activates 8 motors during the day, 3 batteries supply electricity at night. The results of this installation are 4260 W (100 Ah) of power.